Exploiting the rounding mode of ﬂoating-point in the simulation of Chua’s circuit - Silva, M. R.; Nepomuceno, E. G.; Amaral, G. F. V.; Martins, S. A. M.; Nardo, L. G. (Discontinuity, Nonlinearity, and Complexity, 2026)
The Chua’s circuit has been considered as one of the most important paradigms for nonlinear science studies. Its simulations is usually undertaken by means of numerical methods under the rules of IEEE 754-2008 floating-point arithmetic standard. Although, it is well known the propagation error issue, less attention has been given to its consequences on the simulation of Chua’s circuit. In this paper we presented a simulation technique for the Chua’s circuit, it exhibits qualitative differences in traditional approaches such as RK3, RK4 and RK5. By means of the positive largest Lyapunov exponent we show that for the same initial condition and same set of parameters, we produce a periodical and a chaotic solution.